Towards strategy of geoinformation systems and technologies use for territory management - Chabaniuk, V.; Dyshlyk О. (Land Management, Cadastre and Land Monitoring, 2023)
GeoInformation (GI) Systems (GIS) and GI Technologies (GIT, together GIST) have been used for almost half a century, since the creation of Canada’s first GIS in the 60s of the last century, to solve territory management problems. Over the past years, GISTs have reached their maturity, but still continue to develop, covering ever wider areas of use. Even the science of geoinformatics has emerged, in which GIST is used mainly as a toolkit or technology. As an example, geoinformatics in the same Canada is called geomatics and is a technology and/or technological science. At the same time, the expansion of the field of GIST use poses to researchers the question of methods and methodology. They are followed by issues of methods and methodology of geoinformatics not only as a technology, but also as a science. Moreover, these issues become more complicated with the expansion of the field of use. In the information industry, together with the field of use, the term "domain" or "context" is used. Thus, modern GIST usage manipulate a large number of interrelated terms and concepts that are often not clearly defined. The work is devoted to the classification of the main ones, which are influenced by the strategy selected. Spatial models of territory are used in the work. They are used in the study of both territorial systems of reality and individual spatial entities and phenomena of reality. Among spatial models, the main attention is paid to information spatial models, the most famous of which are GeoInformation Systems (GIS). GIS are inseparable from GIS tools - GeoInformation Technologies (GIT). The main results of the article were obtained using the so-called method of Conceptual Frameworks (CoFr) of Spatial Information Systems (SpIS). The CoFr method is applied to a special class of GIS - Atlas Geo-Information Systems (AGIS) of large territories (LT). The AGIS class includes Electronic Atlases (EA), Atlas Information Systems (AtIS), Cartographic Information Systems (CIS) and, in fact, GIS, if we are talking about LT. AGIS-LT is a hierarchical echeloned SpIS, for which the main terms and concepts of the article are applicable. These are such terms and concepts as "strategy" and "methodology" of GIS usage. GIS, in turn, use GIT, which are also classified using CoFr SpIS. Keywords: strategy, methodology, technology, geoinformation systems (GIS), geoinformation technologies (GIT), Atlas GeoInformation System (AGIS), method of Conceptual Frameworks (CoFr)